In praise of music: motets, inscriptions and musical philosophy in Robert Dow's partbooks. - Butler, Katherine (Early Music, 2017)
The Elizabethan music partbooks of Robert Dow, Fellow of All Souls, are notable not only for their elegant calligraphy but also for their inclusion of Latin inscriptions that offer praise for particular composers or comment on the nature of music. Debates surrounding these partbooks have focused on the extent to which they may, or may not, reflect Catholic sympathies on the part of Dow, but this is not the subject of Dow's Latin inscriptions. More apparent is the contribution that these partbooks make to debates regarding the virtues and vices of music-making, a topic that was a particular preoccupation in Oxford circles during the 1580s, just as Dow was copying. Analysing the connection between the inscriptions that draw on myths and commonplaces regarding the powers of music and the motets that they accompany, I argue that these juxtapositions reveal Dow's deep awareness of the issues and rhetoric deployed by recent authors in praise of music. Rather than projecting Catholic sympathies, Dow more obviously presented himself as a defender of music, and his thoughtfully placed inscriptions invited users of these books to reflect on music's role in pious living, good health and honest social pleasures, while also insinuating the unnaturalness and ungodliness of music's critics.